TRADISI PENCULIKAN PENGANTIN PEREMPUAN DALAM FILM ALAA KACHUU: REPRESENTASI KETIDAKSETARAAN GENDER DI KIRGIZSTAN - Lubis, Aprina Luzti; Elfira, Mina (UI Scholars Hub, 2023)
This research investigates how two movies, both entitled Ala Kachuu (2018 and 2002), represent ala kachuu, i.e. a tradition of bride kidnapping in Kyrgyzstan. Even though the Kyrgyz government has formally banned this practice since 2016, which is considered as a form of forced marriage, it still exists and is practiced by some Kyrgyz. This research used the qualitative method coupled with the mise-en-scène cinematographic technique. By using Stuart Hall’s representation theory (1997) and Mansour Fakih’s gender inequality theory (2008) as analysis tools, this study concludes that both movies represent ala kachuu as a tradition which promotes gender inequality. Moreover, they also represent it as a tradition that leads to various forms of violence against women in Kyrgyzstan.